A Semi-Quantitative Repertorial and Philosophical Analysis of Neuro-Psychotic Rubrics in Solanaceae Remedies: Integrating Organon Principles, Miasmatic Theory, and Sensation Approach. - Tiwary, Ekta (Homoeopathic Heritage, 2026)
Background: The Solanaceae family occupies a prominent place in homoeopathic Materia Medica due to its profound action on the nervous system, particularly in acute neuro-psychotic states. Objective: To analyze neuro-psychotic rubrics of major Solanaceae remedies through repertorial evaluation and interpret findings using principles from the Organon of Medicine. Methods: A qualitative repertorial analysis of selected mental rubrics was conducted using classical repertories. Remedies studied included Belladonna, Stramonium, and Hyoscyamus, Capsicum & Tabacum. Rubrics were selected based on intensity, frequency, and clinical relevance. Results: Solanaceae remedies showed strong representation in rubrics related to delirium, fear, violence, and hallucinations. Each remedy demonstrated distinct characteristic expressions within shared themes. Conclusion: Repertorial analysis, when integrated with Organon principles such as Aphorism 153, provides a reliable framework for differentiating Solanaceae remedies in neuro-psychotic conditions.